Peranan Ekstrak Daun Salam Terhadap Angiogenesis Pada Ulkus Traumatikus - Prehananto, Herlambang; Pertami, Sawitri Dwi Indah; Sari, Ernita; Fadhilah, Deffira Tifani Fauz (Bhakta Dental Journal, 2024)
Background: Traumatic ulcers are one of the oral cavity problems that have a large prevalence in society. The use of herbal medicine is still being developed, such as the use of bay leaves which aims to accelerate the healing process. The observable wound healing process is the amount of angiogenesis. Objective: To determine the role of bay leaf extract on angiogenesis in traumatic ulcers. Methods: The design of the laboratory experimental study with a total sample used 18 male rats, which were divided into 3 groups: the treatment group was given 5% bay leaf extract gel, the treatment group was given 7.5% bay leaf extract gel, and 1 control group. Each group consisted of 6 research samples. Results: The results of the One Way Anova test showed a significance value (sig) of 0.000, which means that the value was less than 0.05. Conclusion: Bay leaf extract has a role in increasing the amount of angiogenesis in traumatic ulcers